Analysis of Factors Affecting the Performance of Cimanggis police Personnel, Depok Metro Police, Jakarta, Indonesia - Martandu, Sitti Fatimah Said; Setyabudi, Chairul Muriman; Basir S, Basir S (Devotion : Journal of Research and Community Service, 2023)
The behavior of individuals in the Cimanggis Police Station organization greatly affects the organization directly or indirectly. different abilities of individuals in the face of their tasks or activities. Consistent personnel performance is seen in organizations that pay attention to the environment of personnel carrying out their duties with colleagues, leaders, and the work atmosphere, which can affect a person's ability to carry out their duties. The study aims to determine whether competence and organizational culture mediated by leadership can affect the performance of the Cimanggis Police Station in Depok Jakarta, Indonesia. Using quantitative research cross-sectional study approach. The sample was the entire population of 104 respondents. Data were analyzed using multiple linear regression, hypothesis testing using partial t-test, and simultaneous F-test. The results showed that competence and organizational culture have a significant effect on performance. Competence and organizational culture have a significant influence on leadership. Leadership has a significant effect on the performance of Cimanggis Depok Police personnel, leadership mediates the significant influence of competence on performance, and leadership mediates significantly the influence of organizational culture on performance. The results of the F test simultaneously show that leadership and competence have a significant simultaneous effect on the performance of Cimanggis Depok Police Personnel. It is very necessary to have a clear communication pattern, give appreciation or appreciation to personnel, and provide opportunities for personnel members to make good working relationships, leaders and personnel can jointly provide mutual enthusiasm for work.